Adherence to Treatment of Diabetes in Patients Suffering from Co-Morbid Depression - Bokhari, Sumira Qambar; Niazi, Rizwan Ahmed Khan; Alam, Rehma Shanze; Mazhar, Nauman; Butt, Aysha; Bokhari, Qambar Murtaza (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to explore the adherence to diabetic management in patients with co-morbid depression presenting in Diabetes Management Centre, Services Hospital Lahore and to compare it with adherence to treatment of diabetes in patients not suffering from co-morbid depression. Method: The sample (N=94) was all diabetic patients with either type 1 or type 2 diabetes and presenting at outpatient department, Diabetes Management Centre, Services Hospital Lahore and who are suffering from depression according to DSM-5 Criteria. Cross-sectional study designed was being used. Result: A one-way anova was used. Results showed that there was a significant difference in adherence to treatment between diabetic patient with co-morbid depression and diabetic patient without co-morbid depression at p<.05 for four groups [F (3, 88) =6.108, P=0.001). A Tukey post hoc test revealed that adherence of diabetic patient with no depression (97.43± 14.69) had statistically significant different than diabetic patient with mild depression (77.85± 21.76, p = .002) and moderate depress diabetic patient (80.43±28.20, p = .027). There was no statistically significant difference between diabetic patient without depression and with severe depression (90.27± 21.38, p = .922). Conclusion: The study concluded that diabetic patient without co-morbid depression are better adhered to treatment than those with comorbid depression diabetic patient. The impact of demographic factors should explore in future study.